2010
DOI: 10.1199/tab.0131
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Transferases

Abstract: The 55 Arabidopsis glutathione transferases (GSTs) are, with one microsomal exception, a monophyletic group of soluble enzymes that can be divided into phi, tau, theta, zeta, lambda, dehydroascorbate reductase (DHAR) and TCHQD classes. The populous phi and tau classes are often highly stress inducible and regularly crop up in proteomic and transcriptomic studies. Despite much study on their xenobiotic-detoxifying activities their natural roles are unclear, although roles in defence-related secondary metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
225
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(229 citation statements)
references
References 87 publications
4
225
0
Order By: Relevance
“…Previous research revealed that overexpression of members of the Arabidopsis GST superfamily in Escherichia coli resulted in 25 of the 28 GST tau (U) proteins (GSTUs) causing an aberrant accumulation of acylated GSH thioesters in vivo, a perturbation that was not observed with other GST classes (47). In particular, the study demonstrated that GSTU members catalyzed the S-glutathionylation of 12-oxo-phytodienoic acid (OPDA), an early biosynthetic precursor of JA (28,47). Further research is required to determine whether FIP1 plays a role in other regulatory mechanisms in jasmonic acid signaling, such as preventing epimerization of the active (+)-7-iso-jasmonoyl-L-isoleucine attaching to the inactive (−)-jasmonoyl-L-isoleucine.…”
Section: The Conserved Residues Compose Three Motifs: Motif I (S/t-mentioning
confidence: 86%
See 2 more Smart Citations
“…Previous research revealed that overexpression of members of the Arabidopsis GST superfamily in Escherichia coli resulted in 25 of the 28 GST tau (U) proteins (GSTUs) causing an aberrant accumulation of acylated GSH thioesters in vivo, a perturbation that was not observed with other GST classes (47). In particular, the study demonstrated that GSTU members catalyzed the S-glutathionylation of 12-oxo-phytodienoic acid (OPDA), an early biosynthetic precursor of JA (28,47). Further research is required to determine whether FIP1 plays a role in other regulatory mechanisms in jasmonic acid signaling, such as preventing epimerization of the active (+)-7-iso-jasmonoyl-L-isoleucine attaching to the inactive (−)-jasmonoyl-L-isoleucine.…”
Section: The Conserved Residues Compose Three Motifs: Motif I (S/t-mentioning
confidence: 86%
“…The kinetic assay for GST activity of FIP1 was analyzed by the CDNB assay to determine the production of GS-DNB (28). Protein samples were incubated with 100 mM NaH 2 PO 4 (pH 6.5), 1 mM GSH, and various concentrations of CDNB (0.1-3 mM) at 25°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GSTs in plants have antioxidant properties that can scavenge ROS and other toxic compounds, maintain redox homeostasis, and mediate biosynthesis of certain defense molecules; however, specific function vary by the class [66][67][68]. Our study identified altered expression of seven transcripts putatively associated with GSTs in response to greenbug infestation (Fig.…”
Section: Gsts Peroxidases and Redox State Related Transcriptsmentioning
confidence: 99%
“…GSTF2 related transcripts localized in the plasma membrane encoding phi class of plant-specific proteins mediating phytohormone induced oxidative stress [67,68]. The only GST transcript upregulated in RB (ta.1878.3.s1_at) was putatively associated with membrane associated proteins in eicosanoid and glutathione metabolism (MAPEG-like protein) and is also involved in detoxification functions [69].…”
Section: Gsts Peroxidases and Redox State Related Transcriptsmentioning
confidence: 99%